Analisis Kepuasan Pelanggan Terhadap Beras Organik di PT Mas Kabupaten Bantul Provinsi D.I. Yogyakarta - Indah Widowati (Universitas Sebelas Maret, 2007)
The organic rice that of the future rice to used the food safety for consumers. The organic rice to the trend popular. The aim of the research was to study the effect of kind of consumer and their interaction on available preferency customer of the organic rice at the Supermarket MAS, Bantul Region of Yogyakarta. The result showed that the customer satisfaction very delight until poor delight the influence available of the design package, colour, transportation facility, longevity storage, flavour, physically, and agreement pay system of the rice cutomers. Satisfaction of the household customer level the influence of the physically product, design package and the matter service of the rice organic